The relationship between language learning autonomy extent and learning styles in Malaysian context - Foroutan, Maryam; Noordin, Nooreen; Hamzah, Mohd Sahandri Gani; Baki, Roselan (IDOSI Publications, 2013)
Little research has been done to investigate the relationship between autonomy and learning styles. This paper presents research findings that address the relationship of language learning autonomy with learning styles in eastern context. Data from 360 Form 6 students at Selangor, Malaysia were analyzed by descriptive statistics and Pearson Product-Moment. In addition, stepwise regression procedures were applied to explore the highest to the least contribution of different learning styles to language learning autonomy. The obtained quantitative results indicated that most Malaysian students are auditory learners. Besides, correlational analyses determined that students’ language learning autonomy was significantly and positively related to each learning styles, except individual and group learning styles. Surprisingly, the highest contribution of learning styles to autonomy belonged to auditory and visual learning styles, suggesting that having auditory or visual learning styles do not necessarily limit students’ autonomy extent.